2006
DOI: 10.2174/156800906777441799
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapies in Gynecologic Cancers

Abstract: With the rapid development of high-throughput techniques for identifying novel specific molecular targets in human cancer over the past few years, attention to targeted cancer therapy has dramatically increased. The term "targeted cancer therapy" refers to a new generation of drugs designed to interfere with a specific molecular target that is believed to play a critical role in tumor growth or progression, is not expressed significantly in normal cells, and is correlated with clinical outcome. There has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 176 publications
(220 reference statements)
0
40
0
2
Order By: Relevance
“…Several studies have shown the effect of molecular targeting therapies on ovarian cancers. 5 The most promising molecular targeting therapy is the blockade of angiogenesis using antiangiogenic drugs, such as bevacizumab, which is an antibody to vascular endothelial growth factor (VEGF), and a phase III study combining bevacizumab with first-line chemotherapy is currently ongoing to assess its benefits in ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the effect of molecular targeting therapies on ovarian cancers. 5 The most promising molecular targeting therapy is the blockade of angiogenesis using antiangiogenic drugs, such as bevacizumab, which is an antibody to vascular endothelial growth factor (VEGF), and a phase III study combining bevacizumab with first-line chemotherapy is currently ongoing to assess its benefits in ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are actually inhibitors of PI3K and mTOR that may be used as potential anticancer agents. 41 In summary, hierarchical clustering analysis of genes involved in the PI3K-AKT pathway revealed two subgroups of high-grade endometrial carcinomas …”
mentioning
confidence: 99%
“…In recent years many scientists have concentrated on the question why some patients respond to trastuzumab whereas others do not (Cappuzzo et al, 2006;Chon et al, 2006;Menendez et al, 2006;Tseng et al, 2006). A correlation between the extent of ERBB2 expression determined by immunohistochemistry or FISH and the clinical response has been observed in several studies (Vogel et al, 2002;Mass et al, 2005;Tsuda, 2006).…”
mentioning
confidence: 99%